Estudos eletroanalíticos e mecanísticos de cetoconazol utilizando eletrodo sólido de amálgama de prata(p-AgSAE) - Dantas, Allan Nilson de Sousa (2010)
The aim of this work was to study the electrochemical behavior of antifungal ketoconazole on polished Silver Solid Amalgam Electrode (p-AgSAE).The study began with the evaluation of the best electrolyte for ketoconazole (KC) electrochemical reduction and the Britton–Robinson buffer solution at pH 12 was selected as the best support electrolyte. In the following, with a constant ketoconazole concentration (1.0x10-5 mol L-1) the square wave voltammetric parameters were optimized for the p-AgSAE. The best experimental responses were achieved with 100 s-1 frequency, 25 mV of amplitude and 2 mV of scan increment. The results showed that ketoconazole is reduced in a quasi-reversible process, with one reduction peak at -1.50 V vs. Ag/AgCl/Cl- reference system. After optimized the SWV parameters, the analytical studies were developed in accord to ANVISA for validation the methodology. Linearity range, detection and quantification limits, precision, robustness and accuracy were evaluated. An analytical curve was constructed, that presented a linear region to 4.97x10-7 a 4.30x10-6 mol L-1 with a correlation coefficient to 0.9989. The detection limits for the concentration range were determined as 63.4 μg L-1 while the quantification limits were to 211.5 μg L-1. Studies of accuracy of the methodology were made in different formulations: tablet, cream and shampoo. The values obtained were to 100.8% for the electrolyte, 91% for the tablet, 104% for the cream and 103% for the shampoo. The Relative Standard Deviation (RSD) for the accuracy was less than 5.0%. Quantum chemical calculations were also made with the aim of studying the electronic characteristics of the molecule, and predicting which region of the molecule occurs a electrochemical reduction. It was investigated the distribution of charge on the molecule and the molecular orbital (HOMO and LUMO), which are possible sites of oxidation and reduction, respectively. The LUMO was located on the imidazole ring. In the sequence of the mechanistic elucidation, it was made an exhaustive electrolysis (E = -1,8V during six hours) with monitoring by UV-Vis, being used in the studies that identify the products, the technique of nuclear magnetic resonance espectroscopy, NMR H1. In accord to the study, the reduction of KC occur between the C-N bond on the imidazole ring.